Antibiotics in Chronic Liver Disease and Their Effects on Gut Microbiota - Nahum Mendez-Sanchez; Carlos Esteban Coronel-Castillo; Jacqueline Cordova-Gallardo; Xingshun Qi (MDPI AG, 2023)
Impairments in liver function lead to different complications. As chronic liver disease progresses (CLD), hypoalbuminemia and alterations in bile acid compositions lead to changes in gut microbiota and, therefore, in the host-microbiome interaction, leading to a proinflammatory state. Alterations in gut microbiota composition and permeability, known as gut dysbiosis, have important implications in CLD; alterations in the gut-liver axis are a consequence of liver disease, but also a cause of CLD. Furthermore, gut dysbiosis plays an important role in the progression of liver cirrhosis and decompensation, particularly with complications such as hepatic encephalopathy and spontaneous bacterial peritonitis. In relation to this, antibiotics play an important role in treating CLD. While certain antibiotics have specific indications, others have been subjected to continued study to determine whether or not they have a modulatory effect on gut microbiota. In contrast, the rational use of antibiotics is important, not only because of their disrupting effects on gut microbiota, but also in the context of multidrug-resistant organisms. The aim of this review is to illustrate the role of gut microbiota alterations in CLD, the use and impact of antibiotics in liver cirrhosis, and their harmful and beneficial effects.